Effect of Climate on Volatile Metabolism in ‘Red Globe’ Grapes (Vitis vinifera L.) during Fruit Development - Nan Xiang; Hui Xie; Liuwei Qin; Min Wang; Xinbo Guo; Wen Zhang (Foods, 2022)
With unique flavor and nutritional value, grapes are popular for eating and for the byproducts obtained in their processing. This study cultivated a popular grape variety, ‘Red Globe’, in two regions with different climates to investigate the discrepancies in their volatiles in response to climate. Saccharides, organic acids and transcriptomic and volatile metabolic analyses were studied separately via GC-FID, RNA sequencing and GC-MS/MS methods during the development of grape berries. In total, 83 volatiles were determined in samples, with (E)-2-hexenal the most abundant. Fatty acid derivatives and terpenoids in grapes showed discrepancies in different climates, and some of them were correlated to specific transcription factors. VvWRKY22 was influenced by climate conditions and was relative to saccharide accumulation. MYB-related transcription factors (TFs) were highly correlated with volatiles that accumulated during fruit ripening, especially decanal. Terpenoids showed correlations with a gene module that contained ERFs and HSFs. The findings support the hypothesis that fruit maturity and volatile formations vary in grape berries under different climates. Moreover, specific TFs could participate in volatile accumulations. The given results not only serve to enrich theoretical knowledge on the regulatory mechanism of volatiles in grapes, but also provide guidance for enhancing grape flavor and aroma by modulating cultivational conditions.